Pakistani religious coping and the experience and behaviour of Ramadan - Khan, Ziasma Haneef (Mental health, religion & culture, 2012)
Previous efforts to demonstrate the coping benefits of Muslim beliefs have yielded ambiguous outcomes. With a sample of 200 Pakistani adults, this project used the Islamic Positive Religious Coping and Identification (IPRCI) subscale within the Psychological Measure of Islamic Religiousness (PMIR) to examine relationships with the experience and behaviour of Ramadan. Preliminary confirmatory factor analyses revealed a need to focus on a Positive Islamic Coping factor within the IPRCI. Positive Islamic Coping correlated directly with Positive Ramadan Experience and Ramadan Behaviour and inversely with Negative Ramadan Experience. Along with other PMIR variables assessing Muslim commitments more generally, Positive Islamic Coping helped mediate relationships between Ramadan Experience and Ramadan Behaviour. Punishing Allah Reappraisal from the PMIR displayed only minimal evidence that it recorded a maladaptive form of religious coping. These data confirmed Positive Islamic Coping as an operationalisation of adaptive Muslim coping and illustrated the importance of examining measures that are relevant within a religious tradition.